Relative efficacy and safety of mesenchymal stem cells for osteoarthritis: a systematic review and meta-analysis of randomized controlled trials - Tian, Xiaoyuan; Qu, Zhenan; Cao, Ying; Zhang, Bocheng (Frontiers in Endocrinology, 2024)
The aim of this meta-analysis was to evaluate the efficacy and safety of mesenchymal stem cells (MSCs) for the treatment of knee osteoarthritis (OA). The PubMed, Embase, Cochrane Central Register of Controlled Trials, Scopus and Web of Science databases were searched from inception to May 6, 2024 to identify randomized controlled trials that compared MSCs and placebo or other nonsurgical approaches for treating OA. Two investigators independently searched the literature and extracted data, and conventional meta-analyses were conducted with Review Manager 5.3. The outcomes included pain relief, functional improvement, and risk of adverse events (AEs). A total of 18 articles were included. Overall, MSCs were superior to placebo in terms of relieving pain and improving function at the 12-month follow-up. However, the differences in treatment-related AEs were not significant. The limitations of this study include the high heterogeneity of the included studies. Additionally, the follow-up time in the included studies was relatively short, so more clinical trials are needed to predict the long-term efficacy and safety of MSCs.